Analisis Hubungan Minat Belajar dengan Hasil Belajar Pembuatan Busana Rumah Fase E Tata Busana 1 SMK Negeri 1 Wonoasri - Ainun Salsabila; Peppy Mayasari; Ma’rifatun Nashikhah; Inty Nahari (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to: 1) determine the learning interest of Phase E Fashion Design 1 students, 2) determine the learning outcomes of Phase E Fashion Design 1 students, 3) determine the relationship between learning interest and learning outcomes of Phase E Fashion Design 1 students' home clothing making at SMK Negeri 1 Wonoasri. This study uses a quantitative approach with a correlation method. The sample in this study used a saturated sampling technique, namely all Phase E Fashion Design 1 students of SMK Negeri 1 Wonoasri, totaling 36 students. Data collection was carried out using questionnaires and documentation. Data analysis techniques used include descriptive statistical analysis and hypothesis testing using product moment correlation with the help of the SPSS version 26 program. The results of the study showed that: 1) The learning interest of Phase E Fashion Design 1 students in home clothing making showed a moderate category with a percentage of 66%. 2) The learning outcomes of students of Phase E Fashion Design 1 in home clothing making showed that as many as 20 students (56%) had achieved learning mastery, while 16 students (44%) had not achieved learning mastery. 3) There is a significant positive relationship between learning interest and learning outcomes in making home clothes for students of Phase E Fashion Design 1 of SMK Negeri 1 Wonoasri with a calculated r value greater than r table (0.356 > 0.329) and a significance value of 0.033 <0.05. This indicates that can be accepted, while is rejected.